ETHNOMATHEMATICAL EXPLORATION OF MARTABAK TELUR PREPARATION: A REPRESENTATION OF GEOMETRIC TRANSFORMATION CONCEPTS - Nabila Firda Rahmalia; Fuad Luky Atmaja (Universitas Muhammadiyah Metro, 2026)
The gap between formal mathematics and cultural reality often creates cognitive barriers in geometry learning. This study aims to uncover the concepts of geometric transformation embedded in the production process of Tegal-style Martabak Telur. This research employs a qualitative exploratory approach with a case study design. Data were collected from three Martabak Telur vendors, selected via purposive sampling, using systematic participatory observation and high-precision visual documentation. The data were analyzed using the Miles and Huberman interactive model (reduction, presentation, and verification). The results indicate that the Martabak Telur making process is a concrete representation of dynamic geometry, encompassing: dilation in the dough-flattening technique, rotation and translation in managing heat distribution on the pan, and reflection in the symmetry of the cutting process. These findings hold significant pedagogical value as a foundation for Realistic Mathematics Education (RME), effectively bridging abstract geometric concepts through meaningful cultural contexts. Kesenjangan antara matematika formal dan realitas budaya sering kali menimbulkan hambatan kognitif dalam pembelajaran geometri. Penelitian ini bertujuan untuk mengungkap konsep transformasi geometris yang terdapat dalam proses pembuatan Martabak Telur khas Tegal. Penelitian menggunakan pendekatan kualitatif eksploratif dengan desain studi kasus. Data dikumpulkan dari 3 (tiga) orang penjual Martabak Telur sebagai informan kunci yang dipilih melalui purposive sampling, melalui observasi partisipatif sistematis dan dokumentasi visual berpresisi tinggi. Data dianalisis menggunakan model interaktif Miles dan Huberman. Hasil penelitian menunjukkan bahwa proses pembuatan Martabak Telur merupakan representasi konkret dari geometri dinamis, yang meliputi: dilatasi pada teknik meratakan adonan, rotasi dan translasi dalam mengelola kematangan di wajan, serta refleksi pada simetri pemotongan produk. Temuan ini memiliki signifikansi pedagogis sebagai landasan pengembangan Realistic Mathematics Education (RME), yang efektif menjembatani konsep geometris abstrak melalui konteks budaya yang bermakna bagi siswa.